Qualitative Data Analysis and Fundamental Principles - ÇELİK AHBAB, HİLAL (ANI PUBLISHING, 2020)
In the last years, qualitative research has been increasingly gaining importance in the fields of social sciences. However, the qualitative research and the analysis process are characterized by many uncertainties. Whereas, there are many steps that can guide researchers who want to conduct a qualitative research meticulously in data analysis. These steps allow the qualitative data analysis to fit into a scientific framework. This study is intended to provide a framework for how a qualitative data analysis can be carried out by including the data analysis steps that apply to all qualitative research patterns and the basic principles to be followed. Within this perspective, the main aim of this study is to define the qualitative data analysis, its purpose, the steps of data analysis, the steps of organizing the data, the process of creating categories the interpretation of the qualitative findings and the role of the researcher in qualitative data analysis.
Keywords: Qualitative research; qualitative data analysis; coding; creating categories; qualitative interpretation